Lymph node density is a prognostic factor in patients with major salivary gland carcinoma - SUZUKI, HIDENORI (Oncol Lett, 2015)
Lymph node density (LND) has been reported to be a significant predictor of survival in patients with oral and other carcinomas exhibiting positive lymph nodes. The present study investigated whether the LND is associated with overall survival in subjects with major salivary gland carcinoma. A total of 78 patients newly diagnosed with major salivary gland carcinoma underwent primary tumor resection and neck dissection without preoperative treatment. Of these 78 patients, 32 with pathologically positive lymph nodes were enrolled in the present study. The LND was calculated as the ratio of the number of positive lymph nodes to the number of total lymph nodes. The survival rate was analyzed according to the Kaplan-Meier method. A univariate survival analysis was performed using the log-rank test, and a multivariate survival analysis was performed using the Cox proportional hazards model. An LND of ≥0.38 was found to significantly correlate with a shorter overall survival time in univariate analysis (P=0.017). In multivariate survival analysis, after adjusting for anatomical location (parotid gland/others), an LND of ≥0.38 was identified to be associated with a significantly shorter overall survival time. These results suggest that the LND functions as a prognostic factor in cases of major salivary gland carcinoma.